6x(7-2)=

Simple and best practice solution for 6x(7-2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x(7-2)= equation:


Simplifying
6x(7 + -2) = 0

Combine like terms: 7 + -2 = 5
6x(5) = 0

Reorder the terms for easier multiplication:
6 * 5x = 0

Multiply 6 * 5
30x = 0

Solving
30x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '30'.
x = 0.0

Simplifying
x = 0.0

See similar equations:

| 4x^4-35x^2=9 | | X+20y-40=0 | | -6(2x+1)=-4x+10 | | (253-x)(2x-x)=0.17 | | -9x+18y=36 | | -9y+18y=36 | | 0=r^2-4r+5 | | 4x-3+x=32 | | 4r=r^2+5 | | 60+9x=10x-2 | | (26-2x)(23-2x)=208 | | 3x-6y-42y-140x= | | 16+3x=4x | | 5ln(t+4)=5 | | (2x+3)(2x^2-13x+20)=0 | | 18+5x=7x | | 0=1/2dqrtx | | Z-4(2z+3)=15 | | 5ln(t-4)=5 | | -10=4-7x/3 | | -sin(x)+5cos(x)=4 | | (26-2x)(25-2x)=380 | | 17=2(3x+1)-6 | | 6x+5-2x=4x+4+1 | | i(2-6i)-(4+3i)= | | t-7/6=5/6 | | -3(t-5)+5t=7t-6 | | 5/12=1/3x | | 3x+1.5y=18 | | 3ln(3x)+5=17 | | 1+9(x-4)=7-9(x-5) | | 2(3x-7)-36= |

Equations solver categories